2006
DOI: 10.4028/www.scientific.net/ddf.249.231
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Ga Penetration along Al Grain Boundaries: Effect of External Stress and Ga Undercooling

Abstract: The effects of compressive stress and undercooling of Ga to liquid gallium penetration along grain boundaries (GBs) of aluminum were investigated. It was shown that the penetration rate does not change with the temperature if gallium is in liquid state. The effect of compressive stress applied to Al samples was demonstrated. The time to wetting of all aluminum GBs increased several orders of magnitude if the compressive stress was between 0.1 and 6 MPa. It was proved that solid-liquid transformation does not t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Several studies have shown that the maximum load a polycrystalline Al sample in contact with liquid Ga can sustain decreases as the quantity of Ga on the grain boundaries increases (characterized by exposure time of these Al samples to Ga) eventually leading to intergranular brittle fracture. [1][2][3] Transmission electron microscopy [4][5][6] (TEM), scanning electron microscopy 7,8 (SEM), and synchrotron radiation micro-radiography studies [9][10][11][12] all show that liquid Ga penetrates into grain boundaries in Al at a remarkable rate, leading to a distinct channel morphology. The penetration of liquid Ga along the grain boundaries produces wetting layers with thickness ranging from several monolayers [4][5][6] to several hundred nanometers, [10][11][12] even in the absence of an applied load.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the maximum load a polycrystalline Al sample in contact with liquid Ga can sustain decreases as the quantity of Ga on the grain boundaries increases (characterized by exposure time of these Al samples to Ga) eventually leading to intergranular brittle fracture. [1][2][3] Transmission electron microscopy [4][5][6] (TEM), scanning electron microscopy 7,8 (SEM), and synchrotron radiation micro-radiography studies [9][10][11][12] all show that liquid Ga penetrates into grain boundaries in Al at a remarkable rate, leading to a distinct channel morphology. The penetration of liquid Ga along the grain boundaries produces wetting layers with thickness ranging from several monolayers [4][5][6] to several hundred nanometers, [10][11][12] even in the absence of an applied load.…”
Section: Introductionmentioning
confidence: 99%
“…For example, (t) À1/2 dependence was noted even in the absence of stress. [13,16,17] Incubation times varied from few seconds to several hundred hours depending on the type of GB boundary encountered. In addition, no compression data are available for comparison with tension.…”
Section: ½5mentioning
confidence: 99%